Private sector participation in solid waste management in urban areas in Ghana - Duut, Jacob Mibuika (2011)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirements for the award of Maaster of Science degree in Development Policy and Planning,